Kaupunkien rooli kestävyysmurroksessa : Planetaarisen kaupungistumisen ja kaupunkien aineenvaihdunnan näkökulmat - Ala-Mantila, Sanna; Hirvilammi, Tuuli; Jokela, Salla; Laine, Markus; Weckroth, Mikko (Suomen maantieteellinen seura, 2022)
Cities are increasingly profiling themselves as active agents within the transition towards sustainability. Despite many apparent efforts, discussion on “sustainable cities” has often focused on narrowly defined problems and ignored the interconnectedness of ecological, social, and economic issues that extend beyond the boundaries of formal city regions. Hence, this paper highlights the need for more systemic approaches, taking into account the multifaceted nature of urban sustainability. We use planetary urbanism, urban metabolism, and inclusiveness as conceptual lenses to demonstrate the embeddedness of cities in planetary ecological systems and social structures. We present four examples of urban initiatives that extend from strategic tools to practical urban planning in order to elucidate more holistic ways of thinking about and moving towards, urban sustainability. Our examination calls for rethinking prevailing ideas of cities as forerunners of sustainable development and highlights the need for collaboration for curbing potentially harmful socio-spatial divisions.
Keywords: kestävä kehitys; kaupungistuminen; kestävyys